2009
DOI: 10.1556/abiol.60.2009.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian histology and follicular score in female rats treated with nandrolone decanoate and submitted to physical effort

Abstract: The study was conducted to analyze the histology of the ovaries of adults rats treated with steroids, and submitted or not to physical effort. The control group consisted of females submitted to physical effort and sedentary females, both of which received a physiological solution of 0.9% saline. Treated females, sedentary or not, received 6 mg/kg of body weight of nandrolone decanoate. The steroid and physiological solution were administered intraperitoneally, with a single injection per week for 4 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Over the past decade, AAS use by women increased significantly (Thiblin & Petersson 2004), and its adverse effects include deepening of the voice, growth of body hair, atrophy of the breasts, menstrual irregularities and clitoris hypertrophy (Maravelias et al 2005, Kicman 2008. Studies using animals showed that ND causes changes in the estrous cycle (Gerez et al 2005, Camargo et al 2009a, Chuffa et al 2011c, suppresses the reproductive capacity (Camargo et al 2009b, Belardin et al 2014, and causes changes in the ovarian and uterine histopathology (Gerez et al 2005, Camargo et al 2009a, Chuffa et al 2011c, which may have dose and time-dependent effect (Belardin et al 2014, Simão et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, AAS use by women increased significantly (Thiblin & Petersson 2004), and its adverse effects include deepening of the voice, growth of body hair, atrophy of the breasts, menstrual irregularities and clitoris hypertrophy (Maravelias et al 2005, Kicman 2008. Studies using animals showed that ND causes changes in the estrous cycle (Gerez et al 2005, Camargo et al 2009a, Chuffa et al 2011c, suppresses the reproductive capacity (Camargo et al 2009b, Belardin et al 2014, and causes changes in the ovarian and uterine histopathology (Gerez et al 2005, Camargo et al 2009a, Chuffa et al 2011c, which may have dose and time-dependent effect (Belardin et al 2014, Simão et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…These effects cause follicular apoptosis and ovarian degeneration and atrophy and consequently reduce the volume of the ovary, as we observed in the both this and previous stereological studies ( 21 ). The studies indicate that follicular atresia occurs after AASs abuse ( 11 , 12 ). ND affects the HPG axis and reduces the influence of endocrine factors affecting follicular maturation such as FSH and the resulting LH.…”
Section: Discussionmentioning
confidence: 99%
“…The ovary and uterus weight during treatment and withdrawal period had similar pattern to the body weight of rats. In this respect, Camargo et al (2009) had evaluated the adult female rats that were injected intra-peritoneal with 6 mg/kg nandrolone decanoate (single injection per week for four consecutive days). The results indicated that there have been no significant impact on the uterine weight.…”
Section: Discussionmentioning
confidence: 99%